C.A.V.E shoes and bracing v.1 : the design of clubfoot FAO (Foot Abduction Orthosis) and the improvement of its locking mechanism - Abdullah Sani, Mohd Najib; Sy Yusoff, Syed Muhammad Jaafar (2016)
The current imported FAO is expensive and unaffordable for Congenital Talipes Equinovarus (CTEV) children. Moreover, the design were aesthetically bulky and practically heavy with inelastic rubber. The treatment of footwear products made from local materials innovations is cost effective compared to the imported orthosis. The local products more lightweight and ergonomics in foot support and easy on.